Functional stability and structural transitions of kallikrein: spectroscopic and molecular dynamics studies - Dalal, Sayli; Mhashal, Anil; Kadoo, Narendra; Gaikwad, Sushama M. (Journal of Biomolecular Structure & Dynamics, 2017)
Kallikrein, a physiologically vital serine protease, was investigated for its functional and conformational transitions during chemical (organic solvents, Gdn-HCl), thermal, and pH induced denaturation using biochemical and biophysical techniques and molecular dynamics (MD) simulations approach. The enzyme was exceptionally stable in isopropanol and ethanol showing 110% and 75% activity, respectively, after 96h, showed moderate tolerance in acetonitrile (45% activity after 72h) and much lower stability in methanol (40% activity after 24h) (all the solvents [90% v/v]). Far UV CD and fluorescence spectra indicated apparent reduction in compactness of KLKp structure in isopropanol system. MD simulation studies of the enzyme in isopropanol revealed (1) minimal deviation of the structure from native state (2) marginal increase in radius of gyration and solvent accessible surface area (SASA) of the protein and the active site, and (3) loss of density barrier at the active site possibly leading to increased accessibility of substrate to catalytic triad as compared to methanol and acetonitrile. Although kallikrein was structurally stable up to 90 degrees C as indicated by secondary structure monitoring, it was functionally stable only up to 45 degrees C, implicating thermolabile active site geometry. In GdnHCl [1.0M], 75% of the activity of KLKp was retained after incubation for 4h, indicating its denaturant tolerance. A molten globule-like structure of KLKp formed at pH 1.0 was more thermostable and exhibited interesting structural transitions in organic solvents. The above results provide deeper understanding of functional and structural stability of the serine proteases at molecular level.
Keywords: isopropanol tolerance; Kallikrein; MD Simulation; Molten globule; Serine protease; Thermostability

Identification and functionality prediction of pathogenesis-related protein 1 from legume family - Tellis, Meenakshi; Mathur, Monika; Gurjar, Gayatri; Kadoo, Narendra; Gupta, Vidya (Proteins-Structure Function and Bioinformatics, 2017)
The production and accumulation of pathogenesis-related (PR) proteins in plants is one of the important responses to biotic and abiotic stress. Large number of identified PR proteins has been categorized into 17 functional families based on their structure, phylogenetics, and biological activities. However, they are not widely studied in legume crops. Using 29 PR1 proteins from Arabidopsis thaliana, as query, here we have predicted 92 candidate PR1 proteins through the PSI-BLAST and HMMER programs. These candidate proteins were comprehensively analyzed with, multiple sequence alignment, domain architecture studies, signal peptide, and motif extraction followed by phylogenetic analysis. Further, response of two candidate PR1 proteins from chickpea against Fusarium oxysporum f.sp.ciceri attack was validated using qRT-PCR followed by their 3D structure prediction. To decipher mode of action for PR1s, docking of pathogen extracellular matrix components along with fungal elicitors was performed with two chickpea PR1 proteins. Based on these findings, we propose carbohydrate to be the unique pathogen-recognition feature for PR1 proteins and beta-glucanase activity via beta-glucan binding or modification.

Exploring the biological roles of Dothideomycetes ABC proteins: leads from their phylogenetic relationships with functionally-characterized Ascomycetes homologs - Dube, Gaurav; Kadoo, Narendra; Prashant, Ramya (PLoS One, 2018)
Background The ATP-binding cassette (ABC) superfamily is one of the largest, ubiquitous and diverse protein families in nature. Categorized into nine subfamilies, its members are important to most organisms including fungi, where they play varied roles in fundamental cellular processes, plant pathogenesis or fungicide tolerance. However, these proteins are not yet well-understood in the class Dothideomycetes, which includes several phytopathogens that infect a wide range of food crops including wheat, barley and maize and cause major economic losses. Results We analyzed the genomes of 14 Dothideomycetes fungi (Test set) and seven well-known Ascomycetes fungi (Model set-that possessed gene expression/functional analysis data about the ABC genes) and predicted 578 and 338 ABC proteins from each set respectively. These proteins were classified into subfamilies A to I, which revealed the distribution of the subfamily members across the Dothideomycetes and Ascomycetes genomes. Phylogenetic analysis of Dothideomycetes ABC proteins indicated evolutionary relationships among the subfamilies within this class. Further, phylogenetic relationships among the ABC proteins from the Model and the Test fungi within each subfamily were analyzed, which aided in classifying these proteins into subgroups. We compiled and curated functional and gene expression information from the previous literature for 118 ABC genes and mapped them on the phylogenetic trees, which suggested possible roles in pathogenesis and/or fungicide tolerance for the newly identified Dothideomycetes ABC proteins. Conclusions The present analysis is one of the firsts to extensively analyze ABC proteins from Dothideomycetes fungi. Their phylogenetic analysis and annotating the clades with functional information indicated a subset of Dothideomycetes ABC genes that could be considered for experimental validation for their roles in plant pathogenesis and/or fungicide tolerance.

Global transcriptome analysis of grapevine ( Vitis vinifera L.) leaves under salt stress reveals differential response at early and late stages of stress in table grape cv. Thompson Seedless - Upadhyay, Anuradha; Gaonkar, Tulsi; Upadhyay, Ajay Kumar; Jogaiah, Satisha; Shinde, Manisha P.; Kadoo, Narendra; Gupta, Vidya Shrikant (Plant Physiology and Biochemistry, 2018)
Among the different abiotic stresses, salt stress has a significant effect on the growth and yield of grapevine (Vitis vinifera L.). In this study, we employed RNA sequence based transcriptome analysis to study salinity stress response in grape variety Thompson Seedless. Salt stress adversely affected the growth related and physiological parameters and the effect on physiological parameters was significant within 10 days of stress imposition. A total of 343 genes were differentially expressed in response to salt stress. Among the differentially expressed genes (DEGs) only 42 genes were common at early and late stages of stress. The gene enrichment analysis revealed that GO terms related to transcription factors were over-represented. Among the DEGs, 52 were transcription factors belonging to WRKY, EREB, MYB, NAC and bHLH families. Salt stress significantly affected several pathways like metabolic pathways, biosynthesis of secondary metabolites, membrane transport development related pathways etc. 343 DEGs were distributed on all the 19 chromosomes, however clustered regions of DEGs were present on chromosomes 2, 5, 6 and 12 suggesting probable QTLs for imparting tolerance to salt and other abiotic stresses. Real-time PCR of selected genes in control and treated samples of grafted and own root vines demonstrated that rootstock influenced expression of salt stress responsive genes. Microsatellite regions were identified in ten selected salt responsive genes and highly polymorphic markers were identified using fifteen grape genotypes. This information will be useful for the identification of key genes involved in salt stress tolerance in grape. The identified DEGs could also be useful for genome wide analysis for the identification of polymorphic markers for their subsequent use in molecular breeding for developing salt tolerant grape genotypes.

Effect of media components and growth conditions for improved linoleic acid production by beauveria species - Sanghi, Smrati; Chirmade, Tejas; More, Snehal; Prabhune, Asmita; Gupta, Vidya; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2019)
Beauveria species are well-known insect pathogenic fungi, and Beauveria bassiana is used as a biopesticide against various pests in agriculture. However, the Beauveria species has not been reported as producers of microbial oils. In this study, Beauveria spp. MTCC 5184 was used to produce microbial oil with high linoleic acid (LA) content. Ten experiments were performed to evaluate the effects of several media parameters, such as carbon and nitrogen sources, pH, various concentrations of carbon and nitrogen, growth duration, and oleic acid (OLA) supplementation for maximum LA and dry biomass production by the fungus. Several of these parameters had a significant impact on the production of LA, as well as dry biomass. The glucose yeast extract (GYE) medium supplemented with 1.5% (w/v) peptone yielded maximum LA (0.32 +/- 0.01 g L-1) and biomass (5.51 +/- 0.26 g L-1). However, through the addition of 1.0% (w/v) OLA, the precursor of LA, LA production was enhanced 12-fold (1.24 +/- 0.03 g L-1), and the biomass production increased by 5-fold (11.05 +/- 0.46 g L-1) in comparison to those in the basal (GYE) medium. Using lactose as the sole carbon source produced the lowest LA (0.05 +/- 0.00 g L-1) and biomass (1.04 +/- 0.10 g L-1). The results of this study will be useful for the commercial exploitation of this fungus for the production of LA-rich microbial oil for use in the production of lubricants, greases, paints, cosmetics, etc.

Importance of conserving fragmented forest patches with high diversity of flowering plants in the northern Western Ghats: an example from Maharashtra, India - Kasodekar, Amol; Jadhav, Amol Dilip; Bhagat, Rani; Pawar, Rakesh Mahadev; Gupta, Vidya Shrikant; Kadoo, Narendra (Journal of Threatened Taxa, 2019)
The northern Western Ghats (NWG) comprises of a patchy continuum of forests that have been severely fragmented mainly due to anthropogenic activities. We documented tree diversity within a representative fragmented forest patch of the NWG to study the effects of fragmentation on forest structure and composition. The floristic survey was conducted by replicated strip transect sampling method leading to a total sampling area of 0.3ha. A total of 444 individual trees (Girth>10cm) were sampled, which represented 49 tree species belonging to 42 genera and 23 families. Species richness per unit area and tree density were higher than previously reported values from similar forest type in various regions of NWG. These variations, however, could have resulted due to differences in the sampling area, sampling method, and girth classes used across different studies. Nevertheless, various diversity parameters such as N/S ratio, Simpson’s index, Shannon’s index, and Fisher’s α index were comparable with those reported in previous studies in the Western Ghats. The observed species richness was close to species richness estimates such as abundance-based coverage estimate, Chao-1, and Jackknife estimators. The present study also enumerates 108 species of understory flowering plants, which is provided as a checklist. While access restrictions are imposed in protected areas having high conservation priority, such restrictions are not imposed in non-protected areas, which make them much more vulnerable to anthropogenic activities. Hence, this study recommends that owing to their high diversity, the fragmented forest patches of NWG should also be given high conservation priority.

Phytochemical profile, anti-oxidant, anti-inflammatory, and anti-proliferative activities of Pogostemon deccanensis essential oils - Kumar, Vinay; Shriram, Varsha; Bhagat, Rani; Khare, Tushar; Kapse, Shivanjali; Kadoo, Narendra (3 Biotech, 2019)
Essential oils (EOs) obtained from aerial parts of Pogostemon deccanensis were analyzed for GC-MS profiling, and evaluated for antioxidant, anti-inflammatory, and anti-proliferative activities. GC-MS analysis revealed a total of 47 constituents, establishing the EOs rich in sesquiterpene with >20 sesquiterpenes constituting around 77% of the total EO yield. Major constituents included Curzerene (Benzofuran, 6-ethenyl-4,5,6,7-tetrahydro-3,6-dimethyl-5-isopropenyl-, trans-) (26.39%) and epi-Cadinol (22.68%), Ethanone, 1-(2,4,6-trihydroxyphenyl) (6.83%, Acetophenones), and Boldenone (3.47%, anabolic steroid). EOs found to be rich in phytochemicals attributed for antioxidant potentials of aromatic/medicinal plants, viz., flavonoids (2.71 mu g quercetin equivalents g(-1) EO), total phenols (3.94 mu g gallic acid equivalents (GAE) g(-1) EO), carotenoids (14.3 mu g -carotene equivalents g(-1) EO), and ascorbic acid (2.21 mu g ascorbic acid equivalents g(-1) EO). P. deccanensis EOs exhibited striking antioxidant activities assessed by wide range of assays including ferric reducing antioxidant potential (FRAP, 255.3 GAE at 2 mu g mL(-1) EO), total antioxidant activity (TAA, 264.3 GAE at 2 mu g ml(-1)) of EO, DPPH (65% inhibition at 2 mu g mL(-1)), and OH (58% inhibition at 2 mu g mL(-1)) scavenging. Interestingly, EOs showed considerably higher anti-lipid peroxidation activity than the standard antioxidant molecule ascorbic acid, with 50% protection by 1.29 mu g mL(-1) EO against 20.0 mu g mL(-1) standard. EOs showed strong anti-inflammatory activity with 50% inhibition at 1.95 mu g mL(-1) EO. The anti-proliferative activity of EOs was tested against mouse cancer cell line and the EOs proved a potent anti-proliferative agent with only 2.1% cell survival at 2 mu g mL(-1) EO, whereas the EOs were largely non-toxic-to-normal (non-cancerous) cells with approximately 80% cell survival at the 2 mu g mL(-1) EOs. This being the first attempt of phytochemical profiling and wide array of biological activities of P. deccanensis EOs holds significance as the striking activities were observed at very low concentrations, in some cases at lower than the commercial standards, and has, therefore, great potential for pharmaceutical or commercial exploration.
Keywords: Anti-inflammatory activity; Anti-proliferative activity; Antioxidants; Cytotoxicity; Essential oils

Comparative proteomics unravels the differences in salt stress response of own-rooted and 110R-grafted thompson seedless grapevines - Patil, Sucheta; Shinde, Manisha; Prashant, Ramya; Kadoo, Narendra; Upadhyay, Anuradha; Gupta, Vidya (Journal of Proteome Research, 2020)
Thompson Seedless, a commonly grown table grape variety, is sensitive to salinity when grown on its own roots, and therefore, it is frequently grafted onto salinity-tolerant wild grapevine rootstocks. Rising soil salinity is a growing concern in irrigated agricultural systems. The accumulation of salts near the root zone severely hampers plant growth, leading to a decrease in the productive lifespan of grapevine and causing heavy yield losses to the farmer. In the present study, we investigated the differences in response to salinity between own-rooted Thompson Seedless (TSOR) and 110R-grafted Thompson Seedless (TS110R) grapevines, wherein 110R is reported to be a salt-tolerant rootstock. The grapevines were subjected to salt stress by treating them with a 150 mM NaCl solution. The stress-induced changes in protein abundance were investigated using a label-free shotgun proteomics approach at three time points viz. 6 h, 48 h, and 7 days of salt treatment. A total of 2793 proteins were identified, of which 246 were differentially abundant at various time-points in TSOR and TS110R vines. The abundance of proteins involved in several biological processes such as photosynthesis, amino acid metabolism, translation, chlorophyll biosynthesis, and generation of precursor metabolites was significantly affected by salt stress in both the vines but at different stages of stress. The results revealed that TSOR vines responded fervently to salt stress, while TS110R vines adopted a preventive approach. The findings of this study add to the knowledge of salinity response in woody and grafted plants and hence open the scope for further studies on salt stress-specific differences induced by grafting.
Keywords: 110R rootstock; gene ontology; grafting; label-free proteomics; salt stress; Vitis vinifera

Design of novel drug-like molecules using informatics rich secondary metabolites analysis of Indian medicinal and aromatic plants - Karade, Divya; Vijayasarathi, Durairaj; Kadoo, Narendra; Vyas, Renu; Ingle, P. K.; Karthikeyan, Muthukumarasamy (Combinatorial Chemistry & High Throughput Screening, 2020)
Background: Several medicinal plants are being used in Indian medicine systems from ancient times. However, in most cases, the specific molecules or the active ingredients responsible for the medicinal or therapeutic properties are not yet known. Objective: This study aimed to report a computational protocol as well as a tool for generating novel potential drug candidates from the bioactive molecules of Indian medicinal and aromatic plants through the chemoinformatics approach. Methods: We built a database of the Indian medicinal and aromatic plants coupled with associated information (plant families, plant parts used for the medicinal purpose, structural information, therapeutic properties, etc.) We also developed a Java-based chemoinformatics open-source tool called DoMINE (Database of Medicinally Important Natural products from plantaE) for the generation of virtual library and screening of novel molecules from known medicinal plant molecules. We employed chemoinformatics approaches to in-silico screened metabolites from 104 Indian medicinal and aromatic plants and designed novel drug-like bioactive molecules. For this purpose, 1665 ring containing molecules were identified by text mining of literature related to the medicinal plant species, which were later used to extract 209 molecular scaffolds. Different scaffolds were further used to build a focused virtual library. Virtual screening was performed with cluster analysis to predict drug-like and lead-like molecules from these plant molecules in the context of drug discovery. The predicted drug-like and lead-like molecules were evaluated using chemoinformatics approaches and statistical parameters, and only the most significant molecules were proposed as the candidate molecules to develop new drugs. Results and Conclusion: The supra network of molecules and scaffolds identifies the relationship between the plant molecules and drugs. Cluster analysis of virtual library molecules showed that novel molecules had more pharmacophoric properties than toxicophoric and chemophoric properties. We also developed the DoMINE toolkit for the advancement of natural product-based drug discovery through chemoinformatics approaches. This study will be useful in developing new drug molecules from the known medicinal plant molecules. Hence, this work will encourage experimental organic chemists to synthesize these molecules based on the predicted values. These synthesized molecules need to be subjected to biological screening to identify potential molecules for drug discovery research.
Keywords: Drugs; medicinal plants; Metabolites; scaffolds; text mining; virtual libraries; virtual screening

Plant-pathogen interactions: microRNA-mediated trans-kingdom gene regulation in fungi and their host plants - Mathur, Monika; Nair, Aswathy; Kadoo, Narendra (Genomics, 2020)
MicroRNAs (miRNAs) have been prevalently studied in plants, animals, and viruses. However, recent studies show evidences of miRNA-like RNAs (milRNAs) in fungi as well. It is known that after successful infection, pathogens hijack the host machinery and use it for their own growth and multiplication. Alternatively, resistant plants can overcome the pathogen attack by a variety of mechanisms. Based on this prior knowledge, we computationally predicted milRNAs from 13 fungi, and identified their targets in transcriptomes of the respective fungi as well as their host plants. The expressions of the milRNAs and targets were confirmed using qRT-PCR. We found that plant miRNAs targeted fungal virulence genes, while fungal milRNAs targeted plant resistance genes; corroborating miRNA-mediated trans-kingdom gene regulation and the roles of miRNAs in plantpathogen interactions. Transgenic plants with miRNAs targeting fungal virulence genes, or anti-sense of fungal milRNAs, would be expected to be highly resistant to the fungal pathogens.
Keywords: Disease resistance; Fungal miRNAs; qRT-PCR; Resistance genes; Target prediction; Virulence genes

Antimicrobial synergy of silver-platinum nanohybrids with antibiotics - Ranpariya, Bansi; Salunke, Gayatri; Karmakar, Srikanta; Babiya, Kaushik; Sutar, Santosh; Kadoo, Narendra; Kumbhakar, Pathik; Ghosh, Sougata (Frontiers in Microbiology, 2021)
Various bacterial pathogens are responsible for nosocomial infections resulting in critical pathophysiological conditions, mortality, and morbidity. Most of the bacterial infections are associated with biofilm formation, which is resistant to the available antimicrobial drugs. As a result, novel bactericidal agents need to be fabricated, which can effectively combat the biofilm-associated bacterial infections. Herein, for the first time we report the antimicrobial and antibiofilm properties of silver-platinum nanohybrids (AgPtNHs), silver nanoparticles (AgNPs), and platinum nanoparticles (PtNPs) against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The AgPtNHs were synthesized by a green route using Dioscorea bulbifera tuber extract at 100 degrees C for 5 h. The AgPtNHs ranged in size from 20 to 80 nm, with an average of similar to 59 nm. AgNPs, PtNPs, and AgPtNHs showed a zeta potential of -14.46, -1.09, and -11.39 mV, respectively. High antimicrobial activity was observed against P. aeruginosa and S. aureus and AgPtNHs exhibited potent antimicrobial synergy in combination with antibiotics such as streptomycin, rifampicin, chloramphenicol, novobiocin, and ampicillin up to variable degrees. Interestingly, AgPtNHs could inhibit bacterial biofilm formation significantly. Hence, co-administration of AgPtNHs and antibiotics may serve as a powerful strategy to treat bacterial infections.
Keywords: antibiofilm; antimicrobial synergy; biogenic synthesis; Characterization; silver-platinum nanohybrids

Comparative analysis and structural modeling of elaeis oleifera FAD2, a fatty acid desaturase involved in unsaturated fatty acid composition of american oil palm - Ben Ayed, Rayda; Chirmade, Tejas; Hanana, Mohsen; Khamassi, Khalil; Ercisli, Sezai; Choudhary, Ravish; Kadoo, Narendra; Karunakaran, Rohini (Biology-Basel, 2022)
Simple Summary Palm oil has become the world's most important vegetable oil in terms of production quantity, and its overall demand is exponentially growing with the global population. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing palm oil quality. In this study, we focused on FAD2, a fatty acid desaturase enzyme involved in the desaturation and conversion of oleic acid to linoleic acid in Elaeis oleifera, identified through in silico annotation analysis. Our phylogenetic and comparative studies revealed two SNP markers, SNP278 and SNP851, significantly correlated with the oleic/linoleic acid contents. Our study provides fundamental insights into the mechanism of fatty acids synthesis in oil palm and could support the application of molecular biology techniques to enhance the enzymatic activity and substrate affinity of EoFAD2. American oil palm (Elaeis oleifera) is an important source of dietary oil that could fulfill the increasing worldwide demand for cooking oil. Therefore, improving its production is crucial and could be realized through breeding and genetic engineering approaches aiming to obtain high-yielding varieties with improved oil content and quality. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing oil quality. Our work focused on a fatty acid desaturase (FAD) enzyme involved in the desaturation and conversion of oleic acid to linoleic acid. Following the in silico identification and annotation of Elaeis oleifera FAD2, its molecular and structural features characterization was performed to better understand the mechanistic bases of its enzymatic activity. EoFAD2 is 1173 nucleotides long and encodes a protein of 390 amino acids that shares similarities with other FADs. Interestingly, the phylogenetic study showed three distinguished groups where EoFAD2 clustered among monocotyledonous taxa. EoFAD2 is a membrane-bound protein with five transmembrane domains presumably located in the endoplasmic reticulum. The homodimer organization model of EoFAD2 enzyme and substrates and respective substrate-binding residues were predicted and described. Moreover, the comparison between 24 FAD2 sequences from different species generated two interesting single-nucleotide polymorphisms (SNPs) associated with the oleic/linoleic acid contents.
Keywords: FAD2; Fatty acids; in silico annotation; linoleic acid ratio; oil palm; oleic; SNP; structural modeling

SNP discovery and structural insights into OeFAD2 unravelling high oleic/linoleic ratio in olive oil - Ben Ayed, Rayda; Moreau, Fabienne; Ben Hlima, Hajer; Rebai, Ahmed; Ercisli, Sezai; Kadoo, Narendra; Hanana, Mohsen; Assouguem, Amine; Ullah, Riaz; Ali, Essam A. (Computational and Structural Biotechnology Journal, 2022)
Fatty Acid Desaturase 2 (FAD2), a key enzyme in the fatty acid biosynthesis pathway, is involved in the desaturation and conversion of oleic acid to linoleic acid. Therefore, it plays a crucial role in oleic/linoleic acid ratio and the quality of olive oil. DNA sequencing of 19 FAD2 genes from a set of olive oil varieties revealed several single-nucleotide polymorphisms (SNPs) and highlighted associations between some of the SNPs and saturated fatty acids contents. This was further confirmed by SNP-interaction and machine learning approach. Haplotype diversity analysis led to the discovery of three highly polymorphic SNPs and four haplotypes harboring differential oleic/linoleic acid ratios. Moreover, a combination of molecular modeling and docking experiments allowed a deeper and better understanding of the structure-function relationship of the FAD2 enzyme. Sequence patterns and variations involved in the regulation of the FAD2 activity were also identified. Furthermore, S82C and H213N substitutions in OeFAD2 make the Oueslati variety more interesting in terms of fatty acid profile and oleic acid level. (C) 2022 The Authors. Published by Elsevier B.V. on behalf of Research Network of Computational and Structural Biotechnology.
Keywords: docking; Fatty acid desaturase; Haplotype; machine learning; Oleic/linoleic acid ratio; Protein structure

Tale of two waves: Delineating diverse genomic and transmission landscapes driving the COVID-19 pandemic in Pune, India - Niveditha, Divya; Khan, Soumen; Khilari, Ajinkya; Nadkarni, Sanica; Bhalerao, Unnati; Kadam, Pradnya; Yadav, Ritu; Kanekar, Jugal B.; Shah, Nikita; Likhitkar, Bhagyashree; Sawant, Rutuja; Thakur, Shikha; et al. (Journal of Infection and Public Health, 2023)
Background: Modern response to pandemics, critical for effective public health measures, is shaped by the availability and integration of diverse epidemiological outbreak data. Tracking variants of concern (VOC) is integral to understanding the evolution of SARS-CoV-2 in space and time, both at the local level and global context. This potentially generates actionable information when integrated with epidemiological outbreak data.Methods: A city-wide network of researchers, clinicians, and pathology diagnostic laboratories was formed for genome surveillance of COVID-19 in Pune, India. The genomic landscapes of 10,496 sequenced samples of SARS-CoV-2 driving peaks of infection in Pune between December-2020 to March-2022, were determined. As a modern response to the pandemic, a ``band of five'' outbreak data analytics approach was used. This integrated the genomic data (Band 1) of the virus through molecular phylogenetics with key outbreak data including sample collection dates and case numbers (Band 2), demographics like age and gender (Band 3-4), and geospatial mapping (Band 5).Results: The transmission dynamics of VOCs in 10,496 sequenced samples identified B.1.617.2 (Delta) and BA(x) (Omicron formerly known as B.1.1.529) variants as drivers of the second and third peaks of infection in Pune. Spike Protein mutational profiling during pre and post-Omicron VOCs indicated differential rank ordering of high-frequency mutations in specific domains that increased the charge and binding properties of the protein. Time-resolved phylogenetic analysis of Omicron sub-lineages identified a highly divergent BA.1 from Pune in addition to recombinant X lineages, XZ, XQ, and XM. Conclusions: The band of five outbreak data analytics approach, which integrates five different types of data, highlights the importance of a strong surveillance system with high-quality meta-data for understanding the spatiotemporal evolution of the SARS-CoV-2 genome in Pune. These findings have important implica-tions for pandemic preparedness and could be critical tools for understanding and responding to future outbreaks.& COPY; 2023 Published by Elsevier Ltd on behalf of King Saud Bin Abdulaziz University for Health Sciences. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: COVID-19; Delta; Omicron; SARS-CoV-2 genomic surveillance; Variant of concern; Whole Genome Sequencing (WGS)

Whole genome sequencing and comparative genomics of Indian isolates of wheat spot blotch pathogen bipolaris sorokiniana reveals expansion of pathogenicity gene clusters - Yadav, Sagar; Raazi, Zarrine; Shivaraj, Sheelavanta Matha; Somani, Deepika; Prashant, Ramya; Kulkarni, Abhijeet; Kumar, Rajeev; Biradar, Suma; Desai, Shreenivas; Kadoo, Narendra (Pathogens, 2023)
Spot blotch is a highly destructive disease in wheat caused by the fungal pathogen Bipolaris sorokiniana (teleomorph, Cochliobolus sativus). It is prevalent in warm and humid areas, including Africa, Asia, Latin America, and the USA. In the present study, twelve isolates of B. sorokiniana were collected from wheat fields in three different geographical locations in India. The pathogenicity of seven sporulating isolates was assessed on `DDK 1025', a spot blotch-susceptible wheat variety under greenhouse conditions. The isolate `D2' illustrated the highest virulence, followed by `SI' and `BS52'. These three isolates were sequenced using the Illumina HiSeq1000 platform. The estimated genome sizes of the isolates BS52, D2, and SI were 35.19 MB, 39.32 MB, and 32.76 MB, with GC contents of 48.48%, 50.43%, and 49.42%, respectively. The numbers of pathogenicity genes identified in BS52, D2, and SI isolates were 2015, 2476, and 2018, respectively. Notably, the isolate D2 exhibited a relatively larger genome with expanded arsenals of Biosynthetic Gene Clusters (BGCs), CAZymes, secretome, and pathogenicity genes, which could have contributed to its higher virulence among the tested isolates. This study provides the first comparative genome analysis of the Indian isolates of B. sorokiniana using whole genome sequencing.
Keywords: Bipolaris sorokiniana; CAZyme; comparative genomics; spot blotch; whole genome sequencing

Transcriptome analysis and Structure-Based drug discovery identifies potential biofungicides for controlling Fusarium wilt in chickpea - Sahoo, Rosaleen; Kadoo, Narendra (Journal of Molecular Liquids, 2024)
Fusarium wilt caused by the fungal pathogen Fusarium oxysporum f.sp. ciceri (Foc) is a devastating chickpea disease. Foc is a soil-borne pathogen that invades plants through roots and can kill them in three to four weeks. Although Fusarium wilt can be controlled by soil solarization or fumigation with chemical fungicides, these are not always effective. Soil fumigation is also hazardous to the beneficial soil microflora, deteriorates soil health, and causes pollution. Hence, there is an urgent need to identify potent and environment-friendly biofungicides to control fungal pathogens. We employed transcriptome analysis and structure-based drug discovery approaches to identify potential biofungicides from four widely used medicinal plants: Lantana camara, Piper betel, Ricinus communis, and Azadirachta indica. Fusarium wilt-resistant and susceptible chickpea varieties were pathogeninoculated and grown under controlled conditions in a greenhouse. Transcriptome analysis was performed to identify pathogenicity-related differentially expressed genes (DEGs). Over 600 phytochemicals from the four medicinal plants and four chemical fungicides were considered for molecular docking against the predicted protein structures of the four most expressed pathogen DEGs. The phytochemicals with the best docking scores and the lowest predicted toxicity risk were considered for molecular dynamics (MD) simulation at 100 ns timescale, and 15 potential biofungicides were identified. This study paves the way for developing biofungicides with enhanced efficacy and safety to manage Fusarium wilt in chickpea.
Keywords: Antifungal molecules; Cicer arietinum; fusarium oxysporum; MD Simulation; medicinal plants; Molecular docking

Comprehensive genomic analysis of bipolaris sorokiniana strains: insights into genetic diversity and pathogenicity - Shukla, Anand Kumar; Sahoo, Rosaleen; Kadoo, Narendra (Plant Pathology, 2025)
Bipolaris sorokiniana is an important plant-pathogenic fungus that primarily infects cereals, such as wheat and barley, causing diseases such as spot blotch, common root rot and seedling blight. This study presents a comprehensive comparative genomic analysis of nine B. sorokiniana strains based on 16 genomic parameters, including genome completeness, virulence factors, secondary metabolite biosynthesis, effector proteins and CAZymes, to explore their genetic diversity, genome assembly quality and pathogenic potential. Genomic assemblies of the strains LK93 and ND93-1 exhibited higher N50, L50, BUSCO completeness scores and gene annotations, and were designated as high-quality. Similarly, ND90Pr and BS112 demonstrated a rich arsenal of CAZymes and effector proteins, which indicated their greater infection potential. Variability in biosynthetic gene clusters, especially the presence of isocyanide-NRPS and fungal RiPP clusters, highlights the ecological adaptability and metabolic diversity of these strains. The study also revealed distinct protein family distributions and effector protein repertoires, supporting strain-specific pathogenic strategies. Phylogenetic analyses grouped the strains into three clusters, indicating evolutionary divergence and potential ecological specialisation. The findings of the study underscore the importance of high-quality genomic data and propose LK93 and ND93-1 as more reliable reference genomes for B. sorokiniana. Integrating transcriptomics, proteomics and pathogenicity data, along with expanded strain sampling and unified assembly pipelines, can enhance understanding of the molecular basis of pathogenicity and help develop suitable disease management strategies to control this agriculturally important pathogen.
Keywords: Cochliobolus sativus; comparative genomics; effector proteins; pathogen variability; Secondary metabolites; spot blotch

Ethyl cellulose-based controlled-release atrazine nanoformulation for effective and long-term weed management in agriculture - Gautam, Tripurari Rao; Vasmatkar, Pashupat; Gundloori, Rathna V. N.; Kadoo, Narendra (Industrial Crops and Products, 2025)
Atrazine (ATZ) is the second most widely used herbicide. However, its widespread use is hazardous to the environment. We developed ethyl cellulose-based nanoformulated atrazine (nfATZ) to achieve slow and sustained release of ATZ for long-term weed control in crops such as maize. Maize or corn is used in several industrial applications, including the production of ethanol, corn syrup, adhesives, textiles, biodegradable plastics, etc. As broadleaf weeds significantly impact maize yields, we evaluated the effects of nfATZ and conventional ATZ on tomato as a representative of broadleaf weeds. Various concentrations of ATZ and nfATZ (1-10 mg per kg of soil) were evaluated in pre-emergence, post-emergence, and re-emergence studies. Several morphological, physiological, and biochemical parameters of weeds were assessed, and the efficacy of the herbicide formulations was evaluated. nfATZ outperformed conventional ATZ even at lower concentrations with prolonged herbicidal effectiveness beyond 30 days, while the main crop remained unaffected. The weed mortality in nfATZ treatment was > 80 %, while it was 35 % - 45 % in ATZ treatment. The chlorophyll and carotenoid contents decreased by similar to 65 % in nfATZ-treated weeds, impacting their photosynthesis and overall health. ATZ and nfATZ also significantly impacted the activities of antioxidant enzymes, such as ascorbate peroxidase (similar to 57 %), superoxide dismutase (similar to 67 %), and peroxidase (similar to 77 %) in weeds. Thus, we conclude that nfATZ performed significantly better than ATZ in controlling weeds over the long term and reducing its environmental impact. Therefore, we propose nfATZ for highly effective and long-term weed control in large-scale production of industrial crops like maize.
Keywords: Controlled-release; Herbicide; Nanoformulation; Oxidative stress; Weed management; Weed mortality

Metabolomic profiling unravels the role of sphingolipid pathways in spot blotch resistance in wheat - Yadav, Sagar; Maiti, Saborni; Mundhe, Swapnil; Kadoo, Narendra (Acta Physiologiae Plantarum, 2025)
Spot blotch, caused by the soil- and air-borne fungal pathogen Bipolaris sorokiniana, is a major threat to wheat production. The disease is reaching epidemic proportions in wheat-growing areas, particularly in South Asia, South America, Africa, and Australia. In India, over 25 million hectares of wheat-growing area is threatened by this disease. A systematic study of metabolites can provide insights into the molecular basis of this disease. In the present study, we evaluated the impact of B. sorokiniana inoculation on two wheat varieties, Chirya3 (resistant to spot blotch) and DDK1025 (susceptible to spot blotch). We performed time-course non-targeted metabolite profiling of the pathogen-inoculated and mock-inoculated plants using liquid chromatography coupled with high-resolution mass spectrometry (LC-HRMS). Multivariate analysis was performed to construct a comprehensive statistical workflow, which led to the defined ``metabolomic phenotypes''. Modeling by Orthogonal Projection to Latent Structures-Discriminant Analysis (OPLS-DA) revealed significant metabolites in responses of the resistant and susceptible varieties to pathogen inoculation. A total of 699 metabolites displayed significant variations during the progression of infection. B. sorokiniana-inoculated Chirya3 exhibited high levels of some metabolites, such as sphingolipids, cysteine, phenylalanine, shikimates, etc. The study revealed that sphingolipid pathways are critical in resistance mechanisms contributing to enhanced lignification and disease resistance in wheat.
Keywords: Cochliobolus sativus; High-resolution mass spectrometry; LC-HRMS; Metabolite profiling; OPLS-DA; plant-pathogen interaction

Molecular insights into the oleic acid accumulation in safflower - Salunke, Gayatri; Badhe, Yogesh; Singh, Vrijendra; Ghorpade, Prakash; Hegde, Mahabaleshwar; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2025)
Most of the Indian safflower (Carthamus tinctorius L.) varieties produce oil rich in linoleic acid (LA, similar to 75%) and low in oleic acid (OA, similar to 15%). In the fatty acid biosynthetic pathway, the fatty acid desaturase 2 (FAD2) enzyme converts OA to LA. Safflower is reported to have 12-20 FAD2 genes. Gene expression analysis of four FAD2 genes during seed development in a high LA variety, PBNS-12, revealed high expression of FAD2-1 at 21 days after flowering (DAF), correlating with high LA accumulation. Fatty acid profiling of 448 Indian safflower germplasm accessions revealed four lines to have high (58%-77%) OA content, with NASF-39 having the highest OA content. Interestingly, all four high OA lines showed the same mutation in the FAD2-1 gene. The DNA sequence of FAD2-1 from the four high OA lines showed a deletion of C at the +606 position, resulting in a premature stop codon at the +733 position and a truncated protein of 244 amino acids. Hence, despite the high expression levels of FAD2-1 in NASF-39 at 18-21 DAF, it exhibited high OA (77%). The dysfunctional nature of the truncated FAD2-1 in NASF-39 was evident in molecular docking studies with 1-stearoyl-2-oleoyl phosphatidylcholine. We also sequenced FATB, a thioesterase responsible for releasing stearic acid from acyl carrier protein for further desaturation to oleic acid, where an A773G substitution was observed. This resulted in E258G substitution in NASF-39 FATB compared to that of PBNS-12. This probably made the acyl-binding pocket of NASF-39 FATB unstable, contributing to high OA accumulation. Thus, the outcomes of this study can help develop super and ultra-high oleic safflower varieties through various genetics and genomics approaches.
Keywords: Carthamus tinctorius; FAD2; FATB; Fatty acid desaturase; fatty acid thioesterase; linoleic acid